Penerapan Metode AHP Dalam Sistem Pendukung Keputusan Penempatan Karyawan Menggunakan Aplikasi Expert Choice - Nasibu, Iskandar Z. (Jurnal Pelangi Ilmu, 2009)
Quality of Human Resource is one of factor which to increase performance and productivity in organization or institution. Term t́he right man on the right jobćlearlyly depicts that strategic position in a structural institute ought to be occupied by correct man as according to expertise and knowledge owned by it. This article aim to depict solution toward election problem of employee having achievement to occupy strategic occupation applies approach of the theory AHP (Analytic Hierarchy Process) and uses decision support system éxpert choicet́o assist the side of policy taker in determining placement decision of employee based on placing criterion of occupation which has been specified